2016
DOI: 10.1021/acs.langmuir.6b02940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ablation Rate on the Microstructure and Electrochromic Properties of Pulsed-Laser-Deposited Molybdenum Oxide Thin Films

Abstract: Molybdenum trioxide (MoO) is a well-known electrochromic material. In the present work, n-type α-MoO thin films with both direct and indirect band gaps were fabricated by varying the laser repetition (ablation) rate in a pulsed laser deposition (PLD) system at a constant reactive O pressure. The electrochromic properties of the films are compared and correlated to the microstructure and molecular-level coordination. Mixed amorphous and textured crystallites evolve at the microstructural level. At the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Molybdenum bronze is a collective term used for the colored species that are formed which can be produced by the intercalation of small ions (M + such as Li + , Na + , K + , Rb + , Cs + and H + ) into the van der Waals gap of -MoO 3 , accompanied by the partial reduction of Mo oxidation states. [41a] Molybdenum oxide coloration can be realized by applying a potential (electrochromism), [46] reducing gases such as H 2 (gasochromism), [2b] optical irradiation with appropriate energy (photochromism) [47] or change in temperature (thermochromic). [48] The color change effect can usually be identified as a change in absorbance at a given wavelength before and after coloration.…”
Section: Optical Properties and Chromismmentioning
confidence: 99%
See 2 more Smart Citations
“…Molybdenum bronze is a collective term used for the colored species that are formed which can be produced by the intercalation of small ions (M + such as Li + , Na + , K + , Rb + , Cs + and H + ) into the van der Waals gap of -MoO 3 , accompanied by the partial reduction of Mo oxidation states. [41a] Molybdenum oxide coloration can be realized by applying a potential (electrochromism), [46] reducing gases such as H 2 (gasochromism), [2b] optical irradiation with appropriate energy (photochromism) [47] or change in temperature (thermochromic). [48] The color change effect can usually be identified as a change in absorbance at a given wavelength before and after coloration.…”
Section: Optical Properties and Chromismmentioning
confidence: 99%
“…[93] Analogous to other PVD methods, it has been observed that the deposition parameters such as laser pulse energy, substrate temperature, partial pressure of O 2 gas, and frequency of the laser shots have significant impacts on the crystal structure, lattice strain, stoichiometry, and morphology of the as grown molybdenum oxide thin films. [46]…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh MoO 3 thin film experiences some thermal decomposition during evaporation resulting in lower valence Mo 5+ and Mo 4+ states (Dasgupta et al, 2015;Peelaers et al, 2017;Mrowiecka et al, 2008). ESR (Deb, 1968;Anwar et al, 1989), XPS (Peelaers et al, 2017;Maruyama and Kanagawa, 1995;Santhosh et al, 2017) and NMR (Santhosh et al, 2017;Ritter et al, 1985) measurements show that the localization of surplus electrons is on Mo ions and not on the oxygen vacancies. We also believe that in the sub-stiochiometric oxide thin film (WO 3 , MoO 3 , etc) the charge carrier bound to the W or Mo ion is also strongly coupled to the lattice optical phonons, causing a lattice distortion around the host metallic ion.…”
Section: Polaronic and Bipolaronic Excitations In Moo 3 Thin Filmsmentioning
confidence: 97%
“…To overwhelmed constraint Laser ablation or PLD (schematic of PLD is shown in Figure 10a) had better established to be an unique furthermost suitable techniques for the deposition of thin films comprising an unpredictable through composite stoichiometry. Also PLD has some inimitable advantages such that in-situ temperature controller, partial pressure atmospheric condition, layer by layer coatings, varying the ablation rate exclusively to develop micro/ Nano structured thin film, even this system delivers sufficient microstructure variation and morphologies necessitate for superior electrochemical performance as the most important benefits in PLD are larger deposition rate, precise thickness control unit, capability to functioning in high reactive background gases pressures, and fewer nonconformity from the target composites [50]. The thin film fabrication process parameters of the PLD is exposed in Table 2.…”
Section: Pulsed Laser Depositionmentioning
confidence: 99%